Restricting the flexibility in DEA models - Santos, Jorge (2017)
DEA models have been applied as the benchmarking tool in operations management to empirically account operational and productive efficiency. The wide flexibility in assigning the weights in DEA approach can result on indicators of efficiency who do not take account the relative importance of some inputs. In order to overcome this limitation, in this research we apply the DEA model under restricted weight specification. This model is applied to Spanish hotel companies in order to measure operational efficiency. The restricted weight specification enables us to decrease the influence of assigning unrealistic weights in some units and improve the efficiency estimation and to increase the discriminating potential of the conventional DEA model.